Impact of seasonal variation on lupeol content in latex of Calotropis gigantea R.Br. and Calotropis procera Ait. - Anagha Ranade; Rabinarayan Acharya; Sudipta Roy; Shivangi Bhardwaj (Wolters Kluwer Medknow Publications, 2019)
Background: Ayurveda recommends collection of latex from some plants belonging to Upavisha (semi-poisonous) category in Sharada rutu. The latex from Calotropis gigantea and Calotropis procera (Arka species) finds a significant place, in different therapeutic formulations, with unique mention in management of mukhakaarshnya (hyper pigmentation of face). Aim: To study the impact of seasonal variation on lupeol content of two species of Arka. Material and methods: The latex was collected aseptically during six seasons from two species. After suitable sample preparation, it was used for HPTLC wherein lupeol was used as standard biomarker. Lupeol is a well known bioactive reported for its anti-inflammatory and anti-melanogenic effect on skin. Observations and Results: The lupeol content of Calotropis gigantea was found to be highest in latex sample collected in August-September (Varsha rutu) whereas it was highest in December-January (Hemanta rutu) in Calotropis procera. Conclusion: The findings of highest percentage of lupeol in Saumya rutu i.e Hemanta & Varsha rutu thus coincides with the concept of Kala. It thus proves that seasonal variation has an impact on lupeol content of latex.